The moderating role of perceived risk on trust in e-banking - Wong, David; Loh, Hwee Kuen Claire; Yap, Kenneth; Bak, Randall (School of Marketing, Curtin Business School, 2009)
The purpose of this research is to investigate whether a consumer?s perception of risk in transacting on the internet (Perceived Risk) would have an influence on their trust of a bank?s e-banking website (Specific Trust) and their willingness to use e-banking. The results showed that Perceived Risk has a direct influence on a consumer?s willingness to use e-banking and Specific Trust has a positive moderating influence on the relationship between Perceived Risk and a consumer?s willingness to use e-banking. Consumers who have low perceived risk of transacting on the internet are generally more willing to use e-banking. Their willingness to use e-banking was also shown to be more pronounced in cases where the consumer also trust their bank?s e-banking website. These findings are of particular relevance to banks. It highlights that a consumer?s willingness to use e-banking primarily depends on their perception of risk in transacting on the internet; trust of the specific e-banking website was secondary. This suggests the need for banks to not only employ mechanisms to build trust for their specific e-banking website, but that banks should first take measures to educate their customers and manage general consumer perceptions of the risks of transacting on the internet.